Analisis Hambatan Belajar Pada Materi Pecahan - Ulfa, Nadia; Jupri, Al; Turmudi, Turmudi (RESEARCH AND DEVELOPMENT JOURNAL OF EDUCATION, 2021)
The basic concepts that students have in mathematics need more attention because these basic concepts will have an influence in understanding other mathematical concepts at a higher level. One of the basic concepts in mathematics is the concept of fractions. The concept of fractions was chosen in this study because of several things, first, fractions are an important concept in mathematics, second, the concept of fractions is one of the first abstract concepts that students learn in mathematics, and third, there are still many students who make mistakes when working on problems related to fractions. This study used a qualitative method with a case study design and involved 31 students of grade 7 junior high school in Bandung district. The triangulation technique used in this study is observation, tests, and interviews. The results showed that three were learning obstacle that was found by students including, 1) Ontogenic obstacle which is psychological, where students had weak motivation when learning the concept of fractions, 2) didactical obstacle, where students only gathered on procedural knowledge when learning the concept of fraction, and 3) epistemological obstacle, where there is a limited understanding of students regarding the operations of counting integers with fractions